2021
DOI: 10.3390/rs13081530
|View full text |Cite
|
Sign up to set email alerts
|

Use of Sentinel-2 Satellite Data for Windthrows Monitoring and Delimiting: The Case of “Vaia” Storm in Friuli Venezia Giulia Region (North-Eastern Italy)

Abstract: On the 29th of October 2018, a storm named “Vaia” hit North-Eastern Italy, causing the loss of 8 million m3 of standing trees and creating serious damage to the forested areas, with many economic and ecological implications. This event brought up the necessity of a standard procedure for windthrow detection and monitoring based on satellite data as an alternative to foresters’ fieldwork. The proposed methodology was applied in Carnic Alps (Friuli Venezia Giulia, NE Italy) in natural stands dominated by Picea a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 45 publications
0
13
0
Order By: Relevance
“…In fact, Vaglio Laurin et al (2020) [18] with a bi-temporal change detection approch obtained an overall accuracy of 86% for S2 using an image acquired after 7 months from the storm and 68% for S1 using data acquired after 15-20 days after the storm. Also, Olmo et al (2021) [22] using a bi-temporal approach between vegetation indices (vegetation index differences) calculated on S2 bands produced accurate results in detecting VAIA forest windthrow in Friuli Venezia Gilia. Olmo et al [22] showed with a multitemporal analysis based on vegetation indices that, starting from April 2019, it was possible to observe a deviation of reflectance values for damaged and undamaged areas comparing to the years before the storm.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In fact, Vaglio Laurin et al (2020) [18] with a bi-temporal change detection approch obtained an overall accuracy of 86% for S2 using an image acquired after 7 months from the storm and 68% for S1 using data acquired after 15-20 days after the storm. Also, Olmo et al (2021) [22] using a bi-temporal approach between vegetation indices (vegetation index differences) calculated on S2 bands produced accurate results in detecting VAIA forest windthrow in Friuli Venezia Gilia. Olmo et al [22] showed with a multitemporal analysis based on vegetation indices that, starting from April 2019, it was possible to observe a deviation of reflectance values for damaged and undamaged areas comparing to the years before the storm.…”
Section: Introductionmentioning
confidence: 99%
“…Also, Olmo et al (2021) [22] using a bi-temporal approach between vegetation indices (vegetation index differences) calculated on S2 bands produced accurate results in detecting VAIA forest windthrow in Friuli Venezia Gilia. Olmo et al [22] showed with a multitemporal analysis based on vegetation indices that, starting from April 2019, it was possible to observe a deviation of reflectance values for damaged and undamaged areas comparing to the years before the storm. Piragnolo et al [23] showed that the multitemporal analysis of vegetation indices calculated on the S2 imagery are useful to predict severity classes of damaged areas using aggregational statistics of VIs as input to random forest machine learning algorithm.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Vaia storm, which occurred in Northeastern Italy at the end of October 2018, felled large volumes of timber causing serious ecological and financial losses, with unexpected challenges for forest managers. The wind gusts exceeded 200 km h −1 ; over 490 Municipalities in six administrative Regions registered forest damages over an area of 67,000 km 2 [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
“…The delineation of impacted areas is frequently carried out with optical data [1][2][3]13], even if cloud cover can delay the availability of images for months as previously evidenced also in the Vaia case [14]. Synthetic Aperture Radar (SAR) data may also be employed, even if it requires expert knowledge.…”
Section: Introductionmentioning
confidence: 99%